Determination the Date of Menarche in a Sample of Girls in Karbala City - Hassan, Najat Hamzah (Journal of medical and pharmaceutical sciences, 2019)
The aim of this study is to determine the mean age of menarche among girls in the Karbala city/ Iraq and find the relationship between this age and variables of the study sample. Methodology: Data were collected from 323 girls as a study sample selected randomly from February 2018 to March 2018 from primary and secondary school students. The questionnaire was designed to include two parts, the first part included BMI, educational level, family income. While the second part was specific to the menstruation, including (the first menstrual cycle, menstrual pattern, number of days of menstrual flow, and nature of the menstrual flow). Statistical analysis was carried out using the SPSS program to derive the results of the study (frequencies and percentages, mean and SD, the spearman correlation coefficient to find the relationship and the significance between age at menarche and other variables) Results: The mean age of the girls at menarche was (12.099± 1.390) years and most of them have normal BMI (59.8%), sufficient family income (61.3%.), moderate in nature of the menstrual flow (54.8%) and regular menstruation pattern (75.2%). The days of blood flow (6 and above) day were (70.3%). There is a significant correlation at 0.01 between age at menstruation and BMI, educational level, family income, and a number of days of menstrual flow. While no significant correlation with the menstrual pattern and menstrual flow of the study sample. Conclusions: Age at menarche among girls in Karbala city is similar to that in other countries were (mean± SD) 12.09 ±1.39 years, most of them have normal BMI and normal Menses characteristics. There is a significant correlation between age at menstruation and BMI, educational level, family income, and a number of days of menstrual flow. While no significant correlation with the menstrual pattern and menstrual flow of the study sample. Recommendations: The age of puberty, which is a manifestation of menarche is an important stage in the lives of girls so must be prepared by educating them about the importance of physical health, healthy diet, and exercise that contributes to improving their reproductive health.